Behavioral Indifference Curves - John Komlos (Center for Economic Studies and ifo Institute (CESifo), 2014)
According to the endowment effect there is some discomfort associated with giving up a good, that is to say, we are willing to give up something only if the price is greater than the price we are willing to pay for it. This implies that the indifference curves should designate a reference point at the current level of consumption. Such indifference maps are kinked at the current level of consumption. The kinks in the curves imply that the utility function is not differentiable everywhere and the budget constraint does not always have a unique tangent with an indifference curve. Thus, price changes may not bring about changes in consumption which may be the reason for the frequent stickiness of prices, wages and interest rates. We also discuss a multiple period example in which the indifference map shifts as the reference point shifts implying that the curves cross over time even though tastes do not change.
Keywords: A20; B50; D03; D11; 330; behavioral economics; indifference curves; endowment effect; reference state; gain and loss equivalence; stickiness of prices and wages